Individual monitoring of aerobic and anaerobic performance of hockey players during the annual training cycle - Bolotin A.E.; Poniasov O.E.; Zyukin A.V.; Nguyen K.Z. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to increase functional readiness based on individual assessment of aerobic and anaerobic performance of hockey players throughout the annual training cycle. Methods and structure of the study. Changes in the functional readiness of 15 hockey players of the university student hockey team at the age of 19.5±0.5 years were determined through aerobic and anaerobic testing to assess and correct the direction of the training process in certain periods of the annual training cycle. Results and conclusions. The aerobic power of the players was stable and maintained at a high level throughout the entire macrocycle. Improvement in the aerobic performance of players during the competitive period was reflected in an increase in the level of VO2 max to 55-60 ml/min/kg. A decrease in the parameters of anaerobic performance of the subjects was revealed.